Cholinesterase inhibitors effects in patients with Lewy's bodies associated disease - Custodio, Nilton (2008)
Objectives: To analyze the effects of cholinesterase inhibitors (CHEIs) prescribed for treatment of dementia with Lewy bodies (DLB) and dementia associated with Parkinson’s disease (PDD). Design: Open essay study. Setting: Neurology Service, Hospital Militar Central, and Cognitive Deterioration Diagnosis Unit and Dementia Prevention, Clinica Internacional. Participants: Patients with dementia associated to Lewy bodies and dementia associated with Parkinson’s disease. Interventions: Outcome measures included the Mini-Mental State Examination (MMSE), the Alzheimer Disease Assessment Scale cognitive subscale (ADAS-cog), Alzheimer’s Disease Cooperative Study-Clinical Global Impression of Change (ADCS-CGIC), Alzheimer’s Disease Cooperative Study-Activities of Daily Living Inventory (ADCS-ADL), Neuro-Psychiatry Inventory (NPI), Ten Point Clock-Drawing Test (CDT) and Unified Parkinson´s Disease Rating Scale-motor subscale (UPDRS-part III). Main outcome measures: Patients’ cognitive symptoms, global function and daily life activities. Results: Seventeen patients were treated with rivastigmine, nine with galantamine and seven with donepezil. At six months, rivastigmine-treated patients improved by 1,39 points from baseline on the ADAS-cog, while donepezil and galantamine treated patients showed ‘no change’ (changes of <0,2 points). On the ADCS-ADL, patients treated with rivastigmine, donepezil and galantamine showed decreases of 0,41, 0,68 and 0,86 points, respectively. On the MMSE, donepezil and rivastigmine-treated patients showed ‘no change’ and galantamine-treated patients showed a mean decrease of 1,19 points. The difference with regard to the incidence of parkinsonian symptoms as adverse events was not reflected in significant differences in UPDRS motor scores between the three groups. Side effects were similar in the three treatment groups. Conclusions: Cholinesterase inhibitors may be of benefit for cognitive impairments with impact on global function and activities of daily living in patients with dementia with Lewy bodies and dementia associated with Parkinson’s disease.